The Effect of Special Exercises on Some Physical Abilities Development and Individual Defense Skill Performance in Handball League of 1st Al - Kurk Education - Jabbar, Mohammed; Khamees, Ahmed (Journal of Physical Education, 2020)
The research aimed at identifying the effect of special exercises on the development of some physical abilities and individual defense skills performance. The researchers used the experimental method on (8) handball players from 1st Kurk Education league. Four players were selected for pilot study and the others for the training program. The training program lasted for (6) week making a total (18) sessions. The data was collected and treated using SPSS to conclude that the exercises have a positive effect on developing some physical abilities (arms and legs explosive power and arms and legs speed – strength) and the training program has a positive effect on developing defense skills.